Serum HE4: An Independent Prognostic Factor in Non-Small Cell Lung Cancer - Lamy, Pierre-Jean (PLoS One, 2015)
Human epididymis secretory protein 4 (HE4) is a secreted glycosylated protein encoded by the WAP four-disulfide core domain 2 (WFDC2) gene, located on a chromosome 20 segment that is frequently amplified in many cancers. This study aimed at determining serum HE4 prognostic value in non-small cell lung cancer (NSCLC), following the REMARK guidelines. Serum samples from 346 consecutive patients with histologically proven and previously untreated NSCLC and 41 patients with benign pulmonary disease were collected at the Montpellier-Nimes Academic Hospital. Work-up investigations performed to determine the disease characteristics and treatment algorithms were congruent with international guidelines. HE4 levels in serum were measured with an ELISA test (Fujirebio Diagnostics) that uses two monoclonal antibodies, 2H5 and 3D8, against the C-WFDC domain of HE4. The area under the ROC curve (i.e., overall ability of HE4 to discriminate between controls and patients) was 0.78 (95% confidence interval [CI], 0.738–0.821; z test P <0.0001). Serum HE4 levels were significantly higher in patients with worse performance status, advanced TNM stage and positive nodal status. In the Cox model, overall survival was shorter in patients with high pretreatment serum HE4 (above 140 pmol/L) than in patients with serum H4 level ≤ 140 pmol/L [median survival: 17.7 weeks (95% CI, 11.9 to 24.9) and 46.4 weeks (95% CI, 38.6 to 56.3), respectively; hazard ratio: 1.48 (95% CI, 1.12 to 1.95) for high HE4; adjusted P = 0.0057]. High serum HE4 level at diagnosis is an independent determinant of poor prognosis in NSCLC.